Validity And Reliability In International Language Assessment - Maktuba, Khonsaidova; Khalmuratova Fariza Yelmurad qizi (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This article explores the role of validity and reliability in international language assessment in a clear and practical way. It explains that a good test should not only measure the right skills but also produce consistent results for all test-takers. The discussion focuses on how these two principles influence the quality and fairness of language exams used around the world, including IELTS and TOEFL. The article also highlights simple strategies that can help improve testing systems and make them more accurate, fair, and relevant to real-life language use.